1980
DOI: 10.1177/107110078000100303
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Hypermobile Flatfoot in Children by Molded Insert

Abstract: One hundred feet in 50 children between the ages of 3 and 9 years with a diagnosis of idiopathic hypermobile flatfoot had a custom-molded insert ordered. A specific method of casting, correcting the various components of the deformity was utilized. An 1/8-inch polypropolene insert was fabricated from the positive cast. The insert was worn in leather shoes with a long counter, steel shank, and Thomas heel. The flatfoot was evaluated and classified by measurement of the talometatarsal angle on a standing lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 3 publications
0
39
0
3
Order By: Relevance
“…A variety of supportive devices have been investigated, including heel cups, heel wedges, silicone shoe inserts, and custom shoe orthotics. [33][34][35][36] A prospective study performed by Wenger et al 37 studied the efficacy of shoe modifications in altering the development of the longitudinal arch of the foot in 129 patients aged 3 to 5 years. They were unable to show any significant difference in foot development between patients with shoe wear modifications compared with healthy controls after at least 3 years of follow-up.…”
Section: Asymptomatic Flexible Flatfootmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of supportive devices have been investigated, including heel cups, heel wedges, silicone shoe inserts, and custom shoe orthotics. [33][34][35][36] A prospective study performed by Wenger et al 37 studied the efficacy of shoe modifications in altering the development of the longitudinal arch of the foot in 129 patients aged 3 to 5 years. They were unable to show any significant difference in foot development between patients with shoe wear modifications compared with healthy controls after at least 3 years of follow-up.…”
Section: Asymptomatic Flexible Flatfootmentioning
confidence: 99%
“…There are a few studies that have reported correction of flatfoot with the use of over-the-counter arch supports, heel wedges, and orthotics 33,34 ; however, these studies were greatly limited by the absence of matched controls. Any correction may be due to the natural history of resolution with age.…”
Section: Asymptomatic Flexible Flatfootmentioning
confidence: 99%
“…Several uncontrolled studies in the US have reported that definite permanent increases in arch height can be achieved both clinically and radiographically by the use of ''corrective shoes,'' over-the-counter and custom-molded arch supports, custom orthoses, and heel wedges [40,47]. However, the effect of any intervention cannot be determined without appropriate untreated matched controls.…”
Section: Treatmentmentioning
confidence: 99%
“…A number of studies have concluded that the use of foot orthoses of various designs and approaches are beneficial for children with excessively pronated foot posture [22,[42][43][44][45][46]. Few are specifically focused on growing pains [47,48].…”
Section: Foot Orthotic Interventionmentioning
confidence: 99%